Analisis Saluran Pemasaran dan Kinerja Pasar Pala di Kabupaten Aceh Selatan - Jelliani Jelliani (Universitas Teuku Umar, 2019)
This study aims to :1) the performance of the nutmeg marketing in the south Aceh district. 2) Nutmeg marketing channels in the South Aceh District. The results of this study indicated that the performance of nutmeg marketing occurred in South Aceh District has not been efficient, it could be seen from 54 percent of farmers used the second type of channel in the marketing process. With a marketing margin of Rp.12.633 or 42,11 percent, as well as farmers who used the type one are 25 percent, with a marketing margin of Rp.14.000 or 46,67 percent. The types of nutmeg marketing channels in South Aceh District are of three types of marketing channels.